Nursing Care for Mrs. S Who Experienced Diabetes Mellitus with Nutrition Deficit Problems in the Bougainville Room of the Dr. Koesnadi Bondowoso General Hospital - Wardani, Hamidah Retno; Wulandari, Putri; Agustin, Leni (D'Nursing and Health Journal (DNHJ), 2023)
Background:Diabetes Mellitus is a chronic disease characterized by the body's inability to metabolize carbohydrates, fats and proteins which causes hyperglycemia (high blood glucose levels). Patients with Diabetes Mellitus will experience changes in appetite and experience weight loss. Method: This study uses a case study research design with clients experiencing diabetes mellitus with nutritional deficit problems in the Bougenvil room of the Dr. H. Koesnadi Bondowoso General Hospital, starting from May 15, 2023 to May 17, 2023, data collection in the form of interviews, observations, physical examinations, documentation studies and questionnaires. Results: The results of this study were obtained from research, namely nutritional deficits in accordance with theory, diagnoses in accordance with the theoretical review. In nursing interventions in accordance with the circumstances experienced by the client, while implementation refers to predetermined interventions and evaluation refers to predetermined outcome criteria in accordance with theory and the final evaluation of calories met is rice (735 kcal) and 1 glass of milk (260 kcal). Conclusion: Nutritional deficits are insufficient nutritional intake to meet metabolic needs. The purpose of writing is to provide nursing care to clients who experience diabetes mellitus with nutritional deficit problems.